(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2011)
Recensión de la obra: G. POST, David (2009). In Search of Jefferson´s Moose: Notes on the State of Cyberspace. Oxford: Oxford University Press.